Serum coenzyme Q10 levels are associated with coronary flow reserve in hemodialysis patients - AŞICIOĞLU, EBRU (WILEY, 2013)
Accelerated atherosclerosis is the major cause of mortality in patients on chronic hemodialysis (HD). The aim of this study was to evaluate the relation between coenzyme Q10 (CoQ10) levels and coronary flow reserve (CFR) in HD patients as an indicator of atherosclerosis. Seventy-one chronic HD patients and 65 age- and sex-matched healthy individuals were included in the study. Plasma CoQ10 levels were performed by high-performance liquid chromatography measurements. CFR was assessed by transthoracic Doppler echocardiography. Serum CoQ10 levels (1.36 +/- 0.43 vs. 2.53 +/- 0.55, P<0.001) and CFR values (1.73 +/- 0.11 vs. 2.32 +/- 0.28, P<0.001) were significantly lower in HD patients compared with controls. There was a significant positive correlation between CFR and serum levels of CoQ10 (r=0.669, P<0.001). A linear regression analysis showed that serum levels of CoQ10 were still significantly and positively correlated with CFR (regression coefficient=0.235, P<0.001). Our data have demonstrated that HD patients exhibit decreased plasma CoQ10 levels and CFR values. The study also showed for the first time that serum CoQ10 levels independently predict CFR in HD patients.
Keywords: Coronary flow reserve; coenzyme Q10; hemodialysis; CARDIOVASCULAR RISK-FACTORS; ENDOTHELIAL DYSFUNCTION; OXIDATIVE STRESS; PLASMA; MARKERS; Q(10)